Consideration for nuclear energy in Malaysia - Saad, Mohammad Azannee; Ismail, Fatimah Adila; Md Fauzi, Fatini; Rahmat, Mohd Khairil (IEEE, 2017)
Depletion in Malaysia’s fossil fuels has caused the country to explore other potential energy source. Of all possible options, nuclear power has been considered the best. However, the plan for its implementation has been met with many challenges primarily within the issue of acceptance among public. This paper explores challenges of implementing nuclear power in Malaysia. Data were obtained through interview with professionals that have experience and knowledge in the subject area. Findings highlight lack of agreement among them on Malaysia’s readiness to operate nuclear power plant. This is further looked into aspects that the country must be prepared for should nuclear is set to be implemented.